Rare case of huge vulvar angiomyofibroblastoma in a young female - Tricia Dewi Anggraeni; Laila Nuranna; Muhammad Luthfiyanto; Nuryati Chairani Siregar; Tantri Hellyanti; Trifonia Pingkan Siregar; Leonardo Alexandra (Elsevier, 2021)
Mesenchymal tumours of the vulva are rare and consist of two types, difficult to distinguish but with different prognoses. Angiomyofibroblastoma (AMFB) is a benign tumour, whereas Aggressive Angiomyxoma (AA) is an infiltrating tumour. We describe a 22-year-old nulliparous patient with a vulvar mass sized 19 cm in diameter. After preoperative assessment by ultrasound, chest X-ray, and MRI, wide excision on the tumour was done and diagnosed as AMFB. Differentiation from AA is being discussed.